2017
DOI: 10.1007/s12265-017-9731-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Foreign Body Response to Grow Tissue Engineered Blood Vessels in Vivo

Abstract: It is well known that the number of patients requiring a vascular grafts for use as vessel replacement in cardiovascular diseases, or as vascular access site for hemodialysis is ever increasing. The development of tissue engineered blood vessels (TEBV’s) is a promising method to meet this increasing demand vascular grafts, without having to rely on poorly performing synthetic options such as polytetrafluoroethylene (PTFE) or Dacron. The generation of in vivo TEBV’s involves utilizing the host reaction to an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 98 publications
(130 reference statements)
0
64
0
Order By: Relevance
“…Later, Campbell further developed this concept by using the peritoneal cavity as the in vivo bioreactor [43]. As the knowledge regarding modulation of the FBR increased, this so-called mandril-based method has been fine-tuned and strengthened [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Campbell further developed this concept by using the peritoneal cavity as the in vivo bioreactor [43]. As the knowledge regarding modulation of the FBR increased, this so-called mandril-based method has been fine-tuned and strengthened [8].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of tissue-engineering approaches have been suggested for replacing synthetic grafts [7]. One such method involves the socalled mandril-based approach, which relies on the foreign body response (FBR) driving the development of an autologous in vivo cellularized vascular substitute surrounding an implanted medical device [8]. Using both in vivo [9,10] and in vitro [11] approaches, we previously reported that the implant's surface characteristics can influence the resulting FBR, thereby affecting the composition of the tissue that forms around the implant.…”
Section: Introductionmentioning
confidence: 99%
“…V) Over time remodeling occurs, where the TEBV transdifferentiates to attain characteristics of a native blood vessel. Reproduced with permission . Copyright 2017, Springer Nature.…”
Section: Chemical Phenomenamentioning
confidence: 99%
“…Additionally, the patency of the grafts formed was limited by the occurrence of frequent thrombotic phenomena and the stenotic blockage of the vascular graft. Furthermore, the tubular tissue construct that was formed showed suboptimal mechanical properties and resulted in around a 20% rate of aneurysm formation …”
Section: Chemical Phenomenamentioning
confidence: 99%
“…The experimental studies in this issue address a variety of topics within the heart valve field including two papers on the development of decellularised valves [5,6], the chemical fixation of bovine pericardium and the assessment of a new transcatheter heart valve [7,8]. Within the vascular field, there are two papers, the first addresses the use of an in vivo approach that utilises the host reaction to an implanted biomaterial for the generation of completely autologous tissues, while the second examines the use of intravascular echo as a tool to evaluate the changes within tissue-engineered valves implanted into sheep [9,10]. Engineered tissues can also be used to mimic and study normal and diseased conditions.…”
mentioning
confidence: 99%